Electrocatalytic layers modified by reduced graphene oxide for PEM fuel cells. (9th November 2015) - Pushkarev, A.S.; Pushkareva, I.V.; Grigoriev, S.A.; Kalinichenko, V.N.; Presniakov, M.Yu.; Fateev, V.N.
Abstract: Reduced graphene oxide (RGO) with specific surface area of ca. 600 m 2 /g was synthesized and characterized. A series of membrane-electrode assemblies with RGO addition (in amount from 0 to 6 wt%) to electrocatalytic composition based on 40 wt% of Pt on Vulcan XC-72 were fabricated and tested. Pt/Vulcan XC-72 was synthesized using magnetron-ion sputtering in an impulse mode. It was shown that the optimum content of RGO in the fuel cell active layer is ca. 1 wt%. In particular, at this RGO concentration the maximum fuel cell power density is increased by ca. 8.5% in comparison with no-RGO containing electrocatalytic layers. Highlights: An effective method of RGO synthesis with high specific surface area was developed. Pt/Vulcan XC-72 was synthesized using magnetron-ion sputtering in an impulse mode. Fuel cell with Pt/Vulcan-based electrocatalysts doped by RGO was investigated. The optimum content of RGO in the fuel cell active layer was ca. 1 wt%. The fuel cell maximum power density was increased by ca. 8.5%.